Catalytic performance of texturally improved Al-Mg mixed oxides derived from emulsion-synthesized hydrotalcites - Petrolini, Davi D. [UNESP]; Da Silva Neto, Alano V.; Urquieta-González, Ernesto A.; Pulcinelli, Sandra H. [UNESP]; Santilli, Celso V. [UNESP]; Martins, Leandro [UNESP] (Royal Society of Chemistry (RSC), 2018)
Mixed oxides of aluminum and magnesium derived from hydrotalcites were prepared by means of a sol-gel method mediated by an emulsified sol as pore template. The emulsion consisted of ethanol as the continuous phase and n-dodecane droplets as the dispersed phase, which was stabilized by the presence of the surfactant Pluronic P123. The use of such an emulsion was essential for obtaining materials with a porous structure that were assessed by mercury intrusion porosimetry and nitrogen physisorption. Additional characterization by NH3 and CO2 temperature programmed desorption confirmed that despite the enhancement of their textural properties, the number of acid and base sites was reduced in comparison to a reference and conventionally prepared Al-Mg mixed oxide, as a consequence of the depletion of surface hydroxyls during condensation of the precursors around the nonpolar droplets of the emulsion. Catalytic conversion of 2-propanol under conditions of controlled mass and heat diffusion on the texturally improved Al-Mg mixed oxides evidenced the preparation of a more effective catalyst than the poorly porous reference.